2008
DOI: 10.1371/journal.pntd.0000266
|View full text |Cite
|
Sign up to set email alerts
|

The Interplay between Entamoeba and Enteropathogenic Bacteria Modulates Epithelial Cell Damage

Abstract: BackgroundMixed intestinal infections with Entamoeba histolytica, Entamoeba dispar and bacteria with exacerbated manifestations of disease are common in regions where amoebiasis is endemic. However, amoeba–bacteria interactions remain largely unexamined.MethodologyTrophozoites of E. histolytica and E. dispar were co-cultured with enteropathogenic bacteria strains Escherichia coli (EPEC), Shigella dysenteriae and a commensal Escherichia coli. Amoebae that phagocytosed bacteria were tested for a cytopathic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
80
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 50 publications
1
80
1
Order By: Relevance
“…Interactions between different pathogens have not been commonly studied but two reports suggest that mixed infections that include diarrheagenic E. coli may be exceptionally deleterious [255,256].…”
Section: Clinically Relevant Unanswered Questions About the Biology Omentioning
confidence: 99%
“…Interactions between different pathogens have not been commonly studied but two reports suggest that mixed infections that include diarrheagenic E. coli may be exceptionally deleterious [255,256].…”
Section: Clinically Relevant Unanswered Questions About the Biology Omentioning
confidence: 99%
“…8,9 In addition, it has been demonstrated that amebas can either ingest bacteria or keep them attached to the amebic membrane in a mutualistic interaction that allows the transfer of genetic information to the Entamoeba parasite. 2,3,10,11 Other studies have shown that in the absence of bacteria, E. histolytica does not express virulence factor-associated genes. Long-term axenic cultures of E. histolytica HM1:IMSS show loss of virulence in both in vitro (cytopathic and cytotoxic effects in cell cultures) and in vivo models of infection (amebic liver abscess [ALA] in hamsters).…”
Section: Introductionmentioning
confidence: 99%
“…Modulating factors that regulate the cell cycle 25 , composition of the culture media and bacterial flora 26,27 has not yet successfully yielded infective cysts of E. histolytica. Despite carrying out the in vitro excystation of E. histolytica, factors that induce this process remain poorly understood.…”
Section: Fig 1: Kinetic Excystation Of E Histolytica In Robinson Cumentioning
confidence: 99%